Предмет: Алгебра,
автор: maksimka2271
Помогите пожалуйста очень нужно!!! Дам много баллов!!!!
Приложения:
Ответы
Автор ответа:
0
2x+6-xy-3y=2(x+3)-y(x+3)=(x+3)(2-y)
2x²+2-x³-x⁵=2*(x²+1)-x³*(1+x²)=(x²+1)(2+x³)
3xy-6y-x²+2x=3y(x-2)-x(x-2) =(x-2)(3y-x) x=2 y=-1/3
(x-2)(3y-x) =(2-2)(3*(-1/3)-2)=0*(-3)=0
2x²+2-x³-x⁵=2*(x²+1)-x³*(1+x²)=(x²+1)(2+x³)
3xy-6y-x²+2x=3y(x-2)-x(x-2) =(x-2)(3y-x) x=2 y=-1/3
(x-2)(3y-x) =(2-2)(3*(-1/3)-2)=0*(-3)=0
Похожие вопросы
Предмет: Математика,
автор: houski2020
Предмет: Музыка,
автор: fairyx
Предмет: Русский язык,
автор: Аноним
Предмет: География,
автор: Аноним
Предмет: Биология,
автор: vikatoria123